Implementasi Sistem Siskeudes, Akuntabilitas, dan Transparansi Terhadap Kualitas Laporan Keuangan Desa: Studi Kasus di Desa se-Kecamatan Colomadu - Hendarti Miftahul Jannah; Darmanto; Suprihati (Nur Science Institute, 2026)
This study aims to examine the influence of the implementation of SISKEUDES, Accountability, and Transparency on the Quality of Village Financial Reports in Colomadu District. This study uses the sampling method used, which is purposive sampling, which is a sampling technique that gives an equal opportunity to every element (member) of a population to be selected as a sample member. The sample was reported by a total of 80 respondents. The respondents in this study are Village Apparatus and Regional Community Institutions in Colomadu District. This type of research is quantitative data sources, namely primary data. Based on the results of primary data processing with multiple linear regression analysis methods, the F-test and the t-test have been found that the SISKEUDES, Accountability, and Transparency variables have a significant effect on the Quality of Village Financial Reports.